2019
DOI: 10.5114/pg.2019.88167
|View full text |Cite
|
Sign up to set email alerts
|

The importance of complete blood count parameters in the screening of gastric cancer

Abstract: IntroductionGastric cancer is ranked fourth among all cancers in the world and second in cancer-related deaths. Gastritis leads to the activation of neutrophils, lymphocytes, macrophages, and platelets. Long-term inflammation leads to multistage histopathologic changes called Correa tract, which includes gastritis, atrophy, intestinal metaplasia (IM), dysplasia, and cancer stages.AimTo determine if there is any difference in haematological parameters between gastric cancer (GC) patients, patients with IM, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 25 publications
3
15
0
2
Order By: Relevance
“…LMR or AGR combined with CEA possessed a better AUC than LMR, AGR, or CEA used alone in discriminating colon cancer patients and benign colon diseases cases. Similar to this pilot study, a previous report displayed that LMR possessed a moderate ability (AUC = 0.71) and could contribute to distinguishing patients carrying gastric cancer from those with intestinal metaplasia [23]. In many malignancies, AGR exhibited good diagnostic e cacy (AUC = 0.81) in differentiating cancer patients from healthy controls [29].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…LMR or AGR combined with CEA possessed a better AUC than LMR, AGR, or CEA used alone in discriminating colon cancer patients and benign colon diseases cases. Similar to this pilot study, a previous report displayed that LMR possessed a moderate ability (AUC = 0.71) and could contribute to distinguishing patients carrying gastric cancer from those with intestinal metaplasia [23]. In many malignancies, AGR exhibited good diagnostic e cacy (AUC = 0.81) in differentiating cancer patients from healthy controls [29].…”
Section: Discussionsupporting
confidence: 83%
“…In this retrospective analysis, we found that the colon cancer patients had a lower LMR level than the benign colon disease patients and healthy controls did, and this was consistent with previous ndings. For example, Evrim et al [23] observed that the level of monocyte-to-lymphocyte ratio (MLR) was higher in the gastric cancer group than it was in the intestinal metaplasia and healthy control groups. Luo et al [24] found that MLR was signi cantly elevated in patients carrying urothelial carcinoma of the bladder relative to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] Contrariwise, lymphocyte proliferation is considered a protective factor against tumor growth. [ 36 ] It is important to note that in our research lymphocyte counts were significantly higher in patients with non- H pylori gastritis in comparison to healthy controls and H pylori gastritis. As it is well known that H pylori expresses a carcinogenic potential, [ 38 ] lack of relevant proliferation of lymphocytes in patients from group 1 might suggest a possible long-term malignant transformation.…”
Section: Discussionmentioning
confidence: 49%
“…Recent studies focused on assessing the usefulness of complete blood count parameters as a tool in gastric cancer screening. [ 36 ] Platelets appear to be involved in promoting carcinogenesis, by increasing the secretion of pro-inflammatory cytokines. [ 37 ] Contrariwise, lymphocyte proliferation is considered a protective factor against tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils may promote tumor initiation, progression, and metastasis through the release of several cytokines. IL-17a (a member of the IL-17 family), in particular, is significant in autoimmune diseases and inflammatory processes [91,92]. What makes it particularly interesting is that after binding with its IL-17Ra receptor, IL-17a acts through a novel ACT1-dependent pathway, as opposed to the JAK2-STAT3 pathway triggered by Th1 and Th2 cell families [93][94][95].…”
Section: Il-17amentioning
confidence: 99%